A case of septicemia with meningitis caused by Neisseria weaveri in a 7-year-old child - O.V. Prokopiv; S.A. Lysheniuk; H.M. Karmazin; V.V. Bilavka (Zaslavsky O.Yu., 2024)
A rare case of severe septicemia with meningitis that developed as a result of infection with non-pathogenic Neisseria weaveri, which is better known as the commensal of the dogs' oral cavity, is described in a child aged 7 years. The disease began acutely with fever up to 39 °C and vomiting. Later, these symptoms were accompanied by delusions, psychomotor agitation, sharp pallor of the skin and convulsions. Subsequently, the skin became cyanotic, hemorrhagic rashes appeared throughout the body. With the abovementioned symptoms, the patient was admitted to the intensive care unit of infectious clinical hospital with the diagnosis of meningococcal infection, infectious toxic shock syndrome type 1. As a result of the bacteriological examination of mucus taken from the nasopharynx and cerebrospinal fluid, meningococcus was not detected. However, blood samples contained gram-negative diplococci identified by Vitek-2 and VT2 NH ID cards as Neisseria weaveri. The uniqueness of the case is that in a typical clinical picture of generalized meningococcal infection with hemorrhagic rashes and meningitis, which was accompanied by shock, bacteriological blood tests identified a "zoonotic" type of Neisseria weaveri. As a result of the treatment, clear positive dynamics and eventual recovery of the child on the 14th day of illness were observed. The above case proves that recognition of this microorganism is of clinical importance, and non-pathogenic Neisseria weaveri should be considered as a pathogen that can cause severe septicemia with meningitis and shock manifestations, even without a history of a dog bite. The issue of the role of Neisseria weaveri in the development of the disease in children requires further study and an interdisciplinary approach with the involvement of infectious disease specialists, epidemiologists, immunologists, and microbiologists.